2009
DOI: 10.1002/tox.20469
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal succession of Cylindrospermopsis raciborskii and Aphanizomenon ovalisporum blooms with cylindrospermopsin occurrence in the volcanic Lake Albano, Central Italy

Abstract: The cyanobacterial toxin cylindrospermopsin is rapidly spreading in the European temperate Countries. Cylindrospermopsin was detected for the first time in Italy in 2004; in this study, the presence of this toxin in Albano Lake (Central Italy) has been correlated to the cyanobacterial species Cylindrospermopsis raciborskii and Aphanizomenon ovalisporum and their population dynamics. In 2004, these two species succeeded in the lake during spring, summer, and early autumn without overlapping, causing superficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 63 publications
(70 reference statements)
0
52
2
Order By: Relevance
“…A. ovalisporum is a major source of CYN not only in subtropical and tropical areas of Australia, the United States (Florida), and Israel (9) but also in Mediterranean Europe, where A. ovalisporum can be considered the main CYN producer to date (56)(57)(58). Studies have shown levels of 9.4 to 18 g CYN liter Ϫ1 during A. ovalisporum blooms in Spain and Italy (57,58). A. ovalisporum is characterized by its genetic homogeneity worldwide (9; this study) and an unusually high proportion of CYN-producing strains, although 2 non-CYN-producing strains have recently been reported from Lake Kinneret, Israel (29).…”
Section: Discussionmentioning
confidence: 99%
“…A. ovalisporum is a major source of CYN not only in subtropical and tropical areas of Australia, the United States (Florida), and Israel (9) but also in Mediterranean Europe, where A. ovalisporum can be considered the main CYN producer to date (56)(57)(58). Studies have shown levels of 9.4 to 18 g CYN liter Ϫ1 during A. ovalisporum blooms in Spain and Italy (57,58). A. ovalisporum is characterized by its genetic homogeneity worldwide (9; this study) and an unusually high proportion of CYN-producing strains, although 2 non-CYN-producing strains have recently been reported from Lake Kinneret, Israel (29).…”
Section: Discussionmentioning
confidence: 99%
“…It was first isolated and identified in a cyanobacterium Cylindrospermopsis raciborski but it has been also found in other genera of cyanobacteria, including Anabaena, Aphanizomenon, Raphidiopsis, Lyngbya and Umezakia Banker et al 1997;Li et al 2001;Seifert et al 2007). Up to now the presence of potentially toxic Cylindrospermopsis species on freshwater systems has been reported in different countries such as Portugal (Saker et al 2004), Spain (Quesada et al 2006), France (Brient et al 2009), Italy (Messineo et al 2010), Tunisia (Fathaili et al 2010), etc. This, in conjunction with the potential raising of cyanobacteria blooms due to the climate change (Paerl and Huisman 2008) indicates that the exposure to this cyanotoxin will probably increase in the future.…”
Section: Introductionmentioning
confidence: 96%
“…The population dynamics of cyanobacteria bloom are often characterized by seasonal succession of dominant species (Messineo et al, 2010;Moustaka-Gouni et al, 2007;Tsukada et al, 2006). In China, this phenomenon of seasonal succession of dominant Severe eutrophication of freshwater ecosystem promotes frequent and long-lasting cyanobacteria blooms.…”
Section: Introductionmentioning
confidence: 99%